Inclusive Governance: SICA´ s pending agenda with sexually diverse populations - Solano Aguilar, Gerald (2026)
Introduction. The Central American Integration System (SICA) represents a long-standing initiative aimed at strengthening regional cooperation among member states. However, its implementation has revealed restrictions in the integration of inclusion and human rights agendas, particularly those related to LGBTQI+ communities. Therefore, the main objective of this article is to examine the degree of integration of these populations into SICA’s institutional agenda and to formulate guidelines that promote more inclusive and democratic regional governance.This study uses a descriptive and descriptive-explanatory methodological approach, based on an exhaustive literature review and reflective field diary notes, with the aim of establishing relationships between the variables analyzed and identifying differentiated impacts. The results obtained reveal a lack of explicit policies on sexual diversity, limited citizen participation, and scant generation of disaggregated data. However, opportunities are identified to strengthen the institutionalization of diversity through political dialogue, regional technical cooperation, and coordination between social and governmental actors. Finally, in conclusion, strengthening SICA requires integrating diversity as a structural principle of the integration process, promoting inclusive governance based on human rights and plural participation. Empirical evidence has shown that the effective implementation of diversity in organizational structures and policies is essential for consolidating a sustainable, equitable development model that is genuinely representative of the social plurality that characterizes the Central American region.